2021
DOI: 10.3389/fbioe.2021.643154
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific Finite Element Models of Posterior Pedicle Screw Fixation: Effect of Screw’s Size and Geometry

Abstract: Pedicle screw fixation is extensively performed to treat spine injuries or diseases and it is common for thoracolumbar fractures. Post-operative complications may arise from this surgery leading to back pain or revisions. Finite element (FE) models could be used to predict the outcomes of surgeries but should be verified when both simplified and realistic designs of screws are used. The aim of this study was to generate patient-specific Computed Tomography (CT)-based FE models of human vertebrae with two pedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…In biochemical study, the bone density of the intrapedicular segment has a significantly stronger correlation with pedicle screw pull-out strength than other segments, 24) and the finite element method (FEM) study also reported more von Mises stress at the pedicle than vertebra body. 20,26) Although the use of TP hook as a UIV implant was associated with a lower incidence of proximal junctional kyphosis (PJK) and better functional outcomes than using pedicle screws, 5,9,12) some researches raise questions about its clinical effectiveness. 10,16) Although the importance of pedicle HU has been reported in the spine surgical field, consideration of the UIV bone environment of patients with spinal deformity corrective surgery was insufficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In biochemical study, the bone density of the intrapedicular segment has a significantly stronger correlation with pedicle screw pull-out strength than other segments, 24) and the finite element method (FEM) study also reported more von Mises stress at the pedicle than vertebra body. 20,26) Although the use of TP hook as a UIV implant was associated with a lower incidence of proximal junctional kyphosis (PJK) and better functional outcomes than using pedicle screws, 5,9,12) some researches raise questions about its clinical effectiveness. 10,16) Although the importance of pedicle HU has been reported in the spine surgical field, consideration of the UIV bone environment of patients with spinal deformity corrective surgery was insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…In biochemical study, the bone density of the intrapedicular segment has a significantly stronger correlation with pedicle screw pull-out strength than other segments [ 24 ], and the finite element method study also reported more von Mises stress at the pedicle than vertebra body [ 20 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…After surgical trauma patients will have a significant stress response, and the degree of the stress response can be reflected clinically by the serum CRP index [ 20 ]. In the case of tissue trauma and inflammatory reaction, serum TNF- α expression is enhanced, inflammatory factor activity is increased, and a series of inflammatory cascade reactions will be accompanied, and the body will experience elevated levels of stress hormones in response to external stimuli [ 21 ]. Serum Cor and NE indicators can also reflect the status of the body's stress response with a high sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Another study independently demonstrated that the screw's macrogeometry, specifically screw diameter, significantly contributes to primary stability. 30 Additionally, research has corroborated that cylindrical singlelead thread screws yield superior biomechanical anchorage relative to conical dual-lead thread screws. 31,32 The present study was designed to evaluate both osteotomy instrumentation and pedicle screw design (specifically the individual threads as shown in Figure 1) effect on osseointegration and soft tissue infiltration after 6-and 24-weeks in vivo using a large, pre-clinical animal (sheep) model.…”
Section: Introductionmentioning
confidence: 97%